2007
DOI: 10.1177/1352458506070960
|View full text |Cite
|
Sign up to set email alerts
|

Impact of depression and disability on quality of life in Iranian patients with multiple sclerosis

Abstract: Multiple sclerosis (MS) can influence all aspects of a patient's health. This study determines the main factors affecting quality of life (QoL) in Iranian MS patients. QoL (Multiple Sclerosis Impact Scale; MSIS-29), disability (Expanded Disability Status Scale; EDSS) and depression (Beck Depression Inventory; BDI) were assessed in 106 MS patients. EDSS, clinical course and MS duration significantly correlated with physical MSIS-29. Depression highly correlated with both physical and psychological MSIS-29. Regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 8 publications
5
32
1
1
Order By: Relevance
“…Most studies, however, found that MS patients with higher EDSS scores had significantly higher depression scores, while significant positive correlations were found between the EDSS and depression scores [62][63][64][65][66][67][68]. This is important as MS functional disability and especially depression predict physical health and quality of life [69][70][71]. Our findings showing that depression is associated with progression of MS, as measured with the EDSS over a 5-year period, extend those of previous reports.…”
Section: Discussionsupporting
confidence: 84%
“…Most studies, however, found that MS patients with higher EDSS scores had significantly higher depression scores, while significant positive correlations were found between the EDSS and depression scores [62][63][64][65][66][67][68]. This is important as MS functional disability and especially depression predict physical health and quality of life [69][70][71]. Our findings showing that depression is associated with progression of MS, as measured with the EDSS over a 5-year period, extend those of previous reports.…”
Section: Discussionsupporting
confidence: 84%
“…This means that the reduction in QOL in the physical domain caused reduction in that in the mental domain. In the study by Ayatollahi et al, 33 a significant relationship was observed between psychological factors such as depression and physical health. The highest mean ± SE values of QOL were observed in domains of social function (67.76 ± 2.30), which is in agreement with the results of Haresabadi et al 27 and Taraghi et al 26 Most individuals in this patient sample reported fatigue as a disabling symptom.…”
Section: Demographic and Disease Characteristicsmentioning
confidence: 89%
“…While a number of papers deal with clinical and demographic factors as predictors of the QoL in MS patients [4][5][6][7][8][9][10][11][12], no data are available on the effects of different domains of QoL instruments and the predictive value of comorbid conditions on the QoL. Disease severity (EDSS), disease duration, cognitive function, depression and anxiety have been found to be related to the health-related quality of life (HRQOL) [4].…”
Section: Introductionmentioning
confidence: 99%